The Use of Social Media by Spanish Feminist Organizations: Collectivity From Individualism - Navarro, Celina (2022)
In recent years, social media platforms have become a popular tool for feminist activists and the main medium of communication for new feminist organizations to gain higher visibility. However, along with opportunities, they also bring a reshaping of communication forms and challenges in the modes of organization of these groups, which seek to transform the prevailing individualist logic of the mediated social media landscape into a collective identity. Through the findings of qualitative, semi-structured interviews and the analysis of the content published online, this article looks at the structures of interactions and organizing processes in the social media accounts of new Spanish feminist groups. The findings show that although the committees are aware of the importance of an online presence, they face many obstacles in the creation of collective profiles due to the lack of guidelines, having no clear organized steps on how to post content with consensus within each committee, and the many demands of the speed-driven nature of social media platforms.